Black revolutionary : William Patterson and the globalization of the African American freedom struggle / Gerald Horne. - Horne, Gerald (University of Illinois Press, 2013)
A leading African American Communist, lawyer William L. Patterson (1891-1980) was instrumental in laying the groundwork for the defeat of Jim Crow by virtue of his leadership of the Scottsboro campaign in the 1930s. This watershed biography shows how Patterson helped to advance African American equality by fostering and leveraging international support for the movement.